KEANEKARAGAMAN JENIS FAUNA DARAT PADA KAWASAN WISATA MANGROVE DI DESA LABUAN KECAMATAN LAGE KABUPATEN POSO - Lose, I Made Ismail; Labiro, Elhayat; Sustri, Sustri (Jurnal Warta Rimba, 2015)
The mangrove forest is a forest type that grows in tidal areas (especially in the sheltered beach, lagoons, and estuaries) that vegetation communities tolerate high salinity. The mangrove forest ecosystem is a system consisting of organisms (vegetation, animals, and microorganisms) that interact with the system environment on a mangrove forest habitat. On the basis of this system, the mangrove ecosystem can be seen as a habitat for mangrove vegetation. The research was conducted in the tourist area of mangroves in the village of Labuan. The research was conducted in the tourist area of mangroves in the village of Labuan district of Lage, Poso Regency. This study lasted for 3 months starting from May to July 2014. The data collection technique using the line transect observation location. Based on the observation of terrestrial fauna species in the tourist area of mangrove forest in the village of Labuan, the three types of land fauna that fauna species of birds, reptiles fauna and fauna of invertebrates/insects. Tourist area of mangrove forest in Labuan village is dominated by the number of fauna species of birds (Aves). Species diversity index (H ') of 2. 4314 and evenness index (E) of 0.7080. need for attention and conservation efforts of the government to the location of the tourist area of mangroves in the village of Labuan, see the condition of the area is damaged and not well maintained. Because other than as a tourist area, the area also serves as the habitat of the fauna to live and forage, therefore their rehabilitation and maintenance of back region. Keywords: Diversity Type, Land Fauna, Mangrove.